Impact of Inpatient Harms on Hospital Finances and Patient Clinical Outcomes. Issue 2 (June 2018) - Adler, Lee; Yi, David; Li, Michael; McBroom, Barry; Hauck, Loran; Sammer, Christine; Jones, Cason; Shaw, Terry; Classen, David
Abstract : Objective: The aim of this study was to determine the impact of all-cause inpatient harms on hospital finances and patient clinical outcomes. Research Design: A retrospective analysis of inpatient harm from 24 hospitals in a large multistate health system was conducted during 2009 to 2012 using the Institute of Healthcare Improvement Global Trigger Tool for Measuring Adverse Events. Inpatient harms were detected and categorized into harm (F–I), temporary harm (E), and no harm. Results: Of the 21, 007 inpatients in this study, 15, 610 (74.3%) experienced no harm, 2818 (13.4%) experienced temporary harm, and 2579 (12.3%) experienced harm. A patient with harm was estimated to have higher total cost ($4617 [95% confidence interval (CI), $4364 to 4871]), higher variable cost ($1774 [95% CI, $1648 to $1900]), lower contribution margin (−$1112 [95% CI, −$1378 to −$847]), longer length of stay (2.6 d [95% CI, 2.5 to 2.8]), higher mortality probability (59%; odds ratio, 1.4 [95% CI, 1.0 to 2.0]), and higher 30-day readmission probability (74.4%; odds ratio, 2.9 [95% CI, 2.6 to 3.2]). A patient with temporary harm was estimated to have higher total cost ($2187 [95% CI, $2008 to $2366]), higher variable cost ($800 [95% CI, $709 to $892]), lower contribution margin (−$669 [95% CI, −$891 to −$446]), longer length of stay (1.3 d [95% CI, 1.2 to 1.4]), mortality probability not statistically different, and higher 30-day readmission probability (54.6%; odds ratio, 1.2 [95% CI, 1.1 to 1.4]). Total health system reduction of harm was associated with a decrease of $108 million in total cost, $48 million in variable cost, an increase of contribution margin by $18 million, and savings of 60, 000 inpatient care days. Conclusions: This all-cause harm safety study indicates that inpatient harm has negative financial outcomes for hospitals and negative clinical outcomes for patients. Abstract : Supplemental digital content is available in the text.